Physical properties of electroless nickel-tungsten coating on mild steels obtained from acetic bath - Mahmood, Mahmood Hameed; Harun, Nurliyana; -, Suryanto; Hilmy, Irfan (Trans Tech Publications Ltd., Switzerland, 2015)
Electroless deposition of nickel tungsten on mild steel was conducted using acetic bath, containing nickel sulphate and sodium tungstate in the alkaline medium. The influence of sodium acetate and sodium tungstate on deposits was investigated and characterized using scanning electron microscope (SEM), energy dispersive X-ray spectrometer (EDX) and x-ray diffraction (XRD) to assess the phase, content and microstructure features. The surface roughness of coating was measured using atomic force microscope (AFM) while the hardness was investigated using Vickers microhardness. The results show that deposits have smooth surfaces, Ra = 0.53 µm, with a nanocrystalline structure, crystallite size hardness of deposits decreases as the concentration of sodium tungstate increases.